The Real World Mental Health Needs of Heart Failure Patients Are Not Reflected by the Depression Randomized Controlled Trial Evidence - Tully, Phillip J. (Public Library of Science, 2014)
INTRODUCTION: International depression screening guidelines in heart failure (HF) are partly based on depression treatment efficacy from randomized controlled trials (RCTs). Our aim was to test the external validity of depression RCT criteria in a sample of real-world HF patients. METHODS: HF patients admitted to 3 hospitals in South Australia were referred to a HF psychologist if not already receiving current psychiatric management by psychologist or psychiatrist elsewhere. Screening and referral protocol consisted of the following; (a). Patient Health Questionnaire ≥10; (b). Generalized Anxiety Disorder Questionnaire ≥7); (c). positive response to 1 item panic attack screener; (d). evidence of suicidality. Patients were evaluated against the most common RCT exclusion criteria personality disorder, high suicide risk, cognitive impairment, psychosis, alcohol or substance abuse or dependency, bi-polar depression. RESULTS: Total 81 HF patients were referred from 404 HF admissions, and 73 were assessed (age 60.6±13.4, 47.9% female). Nearly half (47%) met at least 1 RCT exclusion criterion, most commonly personality disorder (28.5%), alcohol/substance abuse (17.8%) and high suicide risk (11.0%). RCT ineligibility criteria was more frequent among patients with major depression (76.5% vs. 46.2%, p<.01) and dysthymia (26.5% vs. 7.7%, p = .03) but not significantly associated with anxiety disorders. RCT ineligible patients reported greater severity of depression (M = 16.6±5.0 vs. M = 12.9±7.2, p = .02) and were higher consumers of HF psychotherapy services (M = 11.5±4.7 vs. M = 8.5±4.8, p = .01). CONCLUSION: In this real-world sample comparable in size to recent RCT intervention arms, patients with depression disorders presented with complex psychiatric needs including comorbid personality disorders, alcohol/substance use and suicide risk. These findings suggest external validity of depression screening and RCTs could serve as a basis for level A guideline recommendations in cardiovascular diseases.